Linkages Between Gender and Rural Transformation in Indonesia - Helena Juliani Purba; Rika Reviza Rachmawati; Aldho Rizki Irawan; Maria Fay Rola‐Rubzen; Tahlim Sudaryanto; Erwidodo Erwidodo; Saktyanu Kristyantoadi Dermoredjo; Umi Karomah Yaumidin (Asia & the Pacific Policy Studies)
ABSTRACT This study explores the linkages between gender and rural transformation in Indonesia. Utilising time‐series data from the National Labour Force Survey from 32 provinces in three different years (2010, 2015, and 2020), we analysed the linkages between rural transformation and gender‐related variables such as womenʼs access to healthcare, education, and technology, gendered income gaps, and womenʼs engagement in agriculture. The results reveal that enhancing education and healthcare accessibility for women can significantly boost their earnings. Basic infrastructure, such as electricity and clean water, is also critical in driving non‐agricultural GDP growth. The findings also show that involving women in rural non‐farm labour is essential for rural transformation, suggesting that policies must focus on gender equality in education, healthcare, and infrastructure access to accelerate economic diversification. Further action is also needed to overcome ongoing gender disparities in womenʼs economic empowerment, such as the prevailing substantial gendered income gap between men and women in rural areas in Indonesia.